Narrating justice and hope: how good stories counter crime and harm - Presser, Lois; Fleetwood, Jennifer; Sandberg, Sveinung (New York University Press, 2025)
"Narrating Justice and Hope takes inspiration from narrative criminology to plumb the potential for stories and storytelling to do good - limiting harm-doing, fostering healing and connection, and suggesting better futures"--